Influence of intravenous lidocaine infusion on haemodynamic response to tracheal intubation and metabolic-hormonal responses during laparoscopic procedures in children: a randomised controlled trial - Maciej Kaszyński; Alicja Kuczerowska; Justyna Pietrzyk; Piotr Sawicki; Paweł Witt; Barbara Stankiewicz; Marek Darowski; Izabela Pągowska-Klimek (BMC Anesthesiology)
Abstract Background Lidocaine, a widely used local anaesthetic, also serves as an adjuvant in pain management. However, its use in children is off-label. This study aimed to determine if intravenous lidocaine alleviates the haemodynamic, metabolic, and hormonal responses to intubation and laparoscopic surgery in children. Methods A single-centre, parallel, double-masked, randomised, placebo-controlled trial. 132 patients, aged 18 months to 18 years, with no contraindications to lidocaine administration and qualified for laparoscopic appendectomy were enrolled. The intervention studied was a lidocaine bolus of 1.5 mg⋅kg− 1 over 5 min given before induction of anaesthesia, followed by intraoperative lidocaine infusion at 1.5 mg⋅kg− 1⋅h− 1 intraoperatively. Patients in the control group were administered a placebo. Mean arterial pressure, glucose, cortisol, lidocaine blood levels, lidocaine-related side effects, and intraoperative opioid requirements were analysed. Results 132 participants completed the trial. The number of patients who experienced an excessive cardiovascular response to induction of anaesthesia or intubation was 23 (37%) in the control group and 21 (34%) in the lidocaine group (p = 0.707). No statistically significant difference was found between the control and lidocaine groups in the hormonal and metabolic responses, as well as intraoperative fentanyl requirements. Serum lidocaine levels remained below the toxic threshold in all patients. Conclusions Although the studied intervention appears to be safe, with no clinical side effects observed and serum lidocaine levels remaining below the toxic threshold, its intraoperative administration is not recommended, as it does not demonstrate any significant benefit during the anaesthesia period when compared to placebo. Trial registration number NCT05238506. The date of first registration: 14/02/2022.